DISPERSIÓN DIFERENCIAL DE SEMILLAS DE HOBOS (SPONDIAS SPP.J POR MICOS CHURUCOS (I.AGOTHRIX I.AGOTHRICHAJ Y SU RELACIÓN CON U MORFOLOGÍA DE lOS FRUTOS (2013)
We determined the seed dispersa] rate of two species of Spondias (S. mombin and S. venulosa) by woolly monkeys at Tinigua National Park, Colombia. Focal sampling was used to quantify the dispersa] pattems during one year. Woolly monkeys disperse seeds of S. mombin more frequently than seeds of S. venulosa (11.2 vs. 0.4 seeds per hour of fruit consumption). In order to find out if differences in shape were correlated with the differences in dispersa] rates of the two species of seeds, we compared severa] morphological features of a sample of 587 seeds and 65 whole fruits, belonging to a total of 23 individualtrees. As seed. width was differerit in the two species; on average, seeds of S. venulosa were wider thanS. mombin seeds. Additionally, a sample of seeds collected frorn the rnonkey's feces indlcated that, on average, seeds dispersed by the rnonkeys are ·srnaller than those available in the forest. The rnorphological differences between the fruits and seeds of the two species of Spondias. are rtpt Iikely to be dlie to .allornetric relationships. The interspecific variation was srnaller than that found between trees of the same species, suggesting a high heritable cornponent in the rnorphological cháracteristics Then, it is possible that woolly rnonkeys in this cornrnunity put a significant selective pressure on the fruit rnorphology of Spondias species. Given their dispersa! patterns, probably they are affecting also the population densities of the plants. Further work on the effect of woolly rnonkeys and other dispersa! agents on the reproductive success of the dispersed is necessary to conf"mn our interpretations.